Demographics, Pension Systems and the Saving-Investment Balance - Chai, Hua (IMF Working Papers; Working Paper, 2018)
This paper studies the effect of demographic change on national saving, global interest rates, and international capital flows, focusing on the role of the public pension system. We develop a small open economy overlapping generations model to illustrate the channels through which demographic variables and pension system generosity interact to affect both private and public saving behavior. We then extend this framework to a two-country setting and simulate scenarios of demographic change and pension reform. We find that the generosity of the pension system plays an important role in determining the movement of the global interest rate and patterns of international capital flows.